2013
DOI: 10.1177/2051415813500954
|View full text |Cite
|
Sign up to set email alerts
|

Is postoperative epidural analgesia better than patient-controlled analgesia for radical cystectomy?

Abstract: Background: The purpose of this study was to evaluate postoperative epidural analgesia (EPA) and intravenous patientcontrolled analgesia (PCA) in terms of morbidity and mortality in patients undergoing radical cystectomy for bladder cancer. Methods: A retrospective study on patients undergoing radical cystectomy for clinical Tis-4N0M0 urothelial carcinoma of the bladder was performed. Patients were separated into two groups: primary EPA or PCA for postoperative analgesia. The surgical complication severity was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…In their single-centre, retrospective analysis of 131 RC patients, Toren et al 30 noted no difference in early outcomes, including pain scores and LOS, between those who received IV PCA and PCEA. Gomez et al 31 similarly showed no differences in complications or survival between RC patients receiving IV PCA and TEA in their retrospective cohort of 274 patients. In a more recent series of 302 patients undergoing RC, aside from modest decreased amounts of total opioid requirement, Winer et al 32 observed no difference in early outcomes-including LOS, return of bowel function, and early complications -between those who received epidural analgesia and those who received other perioperative pain management strategies.…”
Section: Discussionmentioning
confidence: 86%
“…In their single-centre, retrospective analysis of 131 RC patients, Toren et al 30 noted no difference in early outcomes, including pain scores and LOS, between those who received IV PCA and PCEA. Gomez et al 31 similarly showed no differences in complications or survival between RC patients receiving IV PCA and TEA in their retrospective cohort of 274 patients. In a more recent series of 302 patients undergoing RC, aside from modest decreased amounts of total opioid requirement, Winer et al 32 observed no difference in early outcomes-including LOS, return of bowel function, and early complications -between those who received epidural analgesia and those who received other perioperative pain management strategies.…”
Section: Discussionmentioning
confidence: 86%